Plasmon‐Enhanced Silicon Nanowire Array‐Based Hybrid Heterojunction Solar Cells. Issue 7 (6th April 2018) - Banerjee, Debika; Guo, Xiaohang; Cloutier, Sylvain G.
Abstract : In the last decade, freestanding, single crystal silicon nanowires (SiNWs) have attracted significant attention as a potential material for low‐cost optoelectronic devices. In this paper, we demonstrate how strong localized surface plasmon modes, induced using silver nanoparticles, can be used to achieve significant improvement in a simple hybrid organic–inorganic photovoltaic device between n‐type silicon nanowires and poly(3, 4‐ethylenedioxythiophene):poly‐(styrenesulfonate) (PEDOT:PSS). At photon energies above plasmon resonance, metallic nanoparticle‐induced absorption leads to a dramatic reduction of the reflectivity and we report a significant improvement in both the short circuit current density ( J sc ) and the open circuit voltage ( V oc ). This leads to an overall 52% increase in the power conversion efficiencies (PCEs) of the photovoltaic devices when decorating the SiNWs with silver nanoparticles prior to PEDOT:PSS deposition. Abstract : Controlling the cleaning protocol of galvanic displacement method (GDM) to leave minute amounts of Ag nanoparticles attached to the silicon nanowires before coating with solvent treated PEDOT:PSS leads to a significant improvement in short circuit current density and open circuit voltage resulting in 52% overall improvement in the power conversion efficiencies of the photovoltaic devices.